THE DAILY 110 MHZ RADIO WAVE SKY SURVEY: STATISTICAL ANALYSIS OF IMPULSE PHENOMENA FROM OBSERVATION IN 2012-2013 - Samodurov, V. A.; Dumsky, D. V.; Isaev, E. A.; Rodin, A. E.; Kazancev, A. N.; Fedorova, V. A.; Belyatskij, Yu. A. (Одеські астрономічні публікації, 2016)
On the Pushchino Radio Astronomy Observatory of Lebedev Physical Institute by radio telescope BSA (Big Scanning Antenna) in 2012 started daily multi-beam observations at the frequency range 109- 112 MHz. The number of frequency bands range from 6 to 32, while the time constants range from 0.1 to 0.0125 sec. This data is an enormous opportunity for both short and long-term monitoring of various classes of radio sources (including radio transients), the Earth's ionosphere, interplanetary and interstellar plasma monitoring, search and monitoring for different classes of radio sources, etc. A specialized database was constructed to facilitate the large amount of observational data (http://astro.prao.ru/ cgi/out_img.cgi ). We discuss in this paper method of allocation from the database for impulse data of various types. By using the database allocated 83096 individual impulses in declination from +3 to +42 degrees for July 2012 – October 2013 from pulsars, scintillation sources and so one. In result we constructed homogeneous sample suitable for statistical analyzes.